Multi-dietary tracer approach reveals little overlap in foraging ecology between seasonally sympatric ringed and harp seals in the high Arctic - Desforges, Jean-Pierre; Kohlbach, Doreen; Carlyle, Cody G.; Michel, Christine; Loseto, Lisa L.; Rosenberg, Bruno; Yurkowski, David J.; Ferguson, Steven H. (Frontiers in Marine Science, 2022)
The rapid rate of climate change in the Arctic is causing broad-scale changes to the physical environment and biological communities. Characterizing the foraging ecology and habitat use of Arctic marine top predators of high ecological and cultural significance is essential to our understanding of their vulnerability to ecosystem change, especially when there is potential for dietary resource competition in spatially co-occurring species. We therefore undertook this study to explore dietary resource competition between seasonally sympatric ringed seals (Pusa hispida) and harp seals (Pagophilus groenlandicus) in Mittimatalik (previously known as Pond Inlet), Nunavut, Canadian Arctic. We used bulk stable isotopes (δ13C and δ15N), fatty acid-specific carbon isotopes (δ13C), fatty acid profiles, and diatom lipid biomarkers in a multi-tracer framework to track carbon and trophic pathways in liver and muscle of both seal species. Altogether, the dietary tracers showed little overlap in the diet between ringed seals and harp seals when they co-occurred in the open-water season in northwest Baffin Bay. Though a high dependence on sea ice-derived carbon sources for both species was found, dietary tracers suggested that ringed seals relied to a far greater extent on sympagic carbon sources ( 80% vs. 50% for harp seals) and a greater extent of benthic/coastal prey species compared to the more pelagic feeding harp seals. Ringed seal samples were available year-round, and analyses revealed a clear seasonal pattern of foraging on sympagic and benthic prey during ice-covered months of the year and shifting to greater reliance on pelagic prey during the summer open-water season. Overall, ringed seals may be more vulnerable to changes in sea-ice dynamics in the rapidly changing Arctic than harp seals, though it remains difficult to predict future dietary plasticity and competition between co-occurring top predators in an increasingly ice-free Arctic with a changing prey community.